Protocol of Process Evaluation of Secondary Prevention by Structured Semi-Interactive Stroke Prevention Package in India (SPRINT INDIA)Trial. (13th April 2022) - Verma, Shweta J.; Gulati, Puja; Khatter, Himani; Arora, Deepti; Dhasan, Aneesh; Sharma, Meenakshi; Sylaja, Padmavathyamma Narayanapillai; Pandian, Jeyaraj D.
Background and aims: Secondary Prevention by Structured Semi-Interactive Stroke Prevention Package in India (SPRINT India) is a complex intervention delivered across 30 centres in 16 Indian states. The study delivers intervention in 12 languages in the form of workbook, videos and short messaging using cellular device and internet as a tool. Objectives of process evaluation are to assess whether trial was implemented as planned (fidelity and dose); whether, how and why the intervention is effective by looking at the stakeholders' experiences (effectiveness); to assess reach of intervention in population (reach); how intervention fits into treatment plan to cause behavioural change when adopted (adoption); usefulness for target population and bring behaviour change (maintenance). Methods: SPRINT India process evaluation is a prospective, multicentre study conducted with mixed-methods approach. Sample size of centres and stakeholders will be selected by maximum variance purposive sampling strategy. Centres will be stratified primarily for representing the 11 regional language in which the intervention is delivered. Qualitative data will comprise of interviews of patients, care givers and health professionals at these centres using semi structured interview guide. Quantitative data will comprise of all the randomised patients. Process evaluation framework is based on Realist and RE-AIM evaluation models presented according to Medical Research Council's guidance. The four sections of the framework are context, trial implementation, mechanisms of impact and trial outcomes. Results: Interviews of approximately 100 stakeholders and focus group interviews of health professionals and SPRINT India study central coordinating staff will be conducted. Analysis will be done using triangulation methodology. It will incorporate use of both quantitative and qualitative data, data collection techniques, data sources, evaluation models, stakeholders and researchers. Conclusions: Process evaluation will identify efficacious factors in intervention package and consolidate use of secondary stroke semi-interactive stroke prevention package into practice and policy to prevent recurrent stroke.